Embedding Technologies into the Farming Economy: Extension Work of Japanese Sugar Companies in Colonial Taiwan. Issue 1 (1st March 2018) - Tsuru, Shuntaro
Abstract: This article examines the extension of cultivation technologies by Japanese sugar companies in colonial Taiwan during the 1910s. As it became necessary for them to price their sugar more competitively in a Japanese market that by the end of the 1900s had become oversupplied, and with the devastation wrought to sugarcane cultivation by severe storms, from the early 1910s sugar companies accelerated their efforts to extend technologies to sugarcane farmers. However, such attempts faced difficulties at first because of the economic conditions at the time and also because of conflict with the production system managed by each farming household, which was characterized by multiple farming, crop rotation, and a circular economy. Realizing the deficiencies in extending the technology, Ensuikō Sugar began to reform its work from the mid-1910s so as to win the hearts of the farmers by reorganizing the hierarchy involved in the extension efforts The company also redesigned the components of its extension work by taking account of the economy of Taiwanese farmers. This article observes the beginning of the incorporation of the farming economy into a system of agricultural technology, in which the power involved in technologies gradually permeated the daily lives of farmers.